2021
DOI: 10.3389/fendo.2021.633625
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effects of NPY1 Receptor Activation on Islet Structure Are Driven by Pancreatic Alpha- and Beta-Cell Transdifferentiation in Diabetic Mice

Abstract: Enzymatically stable and specific neuropeptide Y1 receptor (NPYR1) agonists, such as sea lamprey PYY(1-36) (SL-PYY(1-36)), are believed to improve glucose regulation in diabetes by targeting pancreatic islets. In this study, streptozotocin (STZ) diabetic transgenic GluCreERT2;ROSA26-eYFP and Ins1Cre/+;Rosa26-eYFP mouse models have been used to study effects of sustained NPYR1 activation on islet cell composition and alpha- and beta-cell lineage transitioning. STZ induced a particularly severe form of diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…18 However, the characteristic expansion of alpha-cell area and central internalisation of glucagon positively stained islet cells induced by STZ 48 were reversed only in the combined treatment group. Similar observations have been made previously with sub-chronic NPY1R activation, 21 suggesting restoration of the local islet environment, rather than augmentation of beta-cell mass alone, is a key benefit of NPY1R activation by SL-PYY. Indeed, positive effects on beta-cell turnover were not different between treatment groups and observed effects on beta-cell proliferation and protection against apoptosis agree with earlier studies on the effects of these peptides on beta-cell health.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…18 However, the characteristic expansion of alpha-cell area and central internalisation of glucagon positively stained islet cells induced by STZ 48 were reversed only in the combined treatment group. Similar observations have been made previously with sub-chronic NPY1R activation, 21 suggesting restoration of the local islet environment, rather than augmentation of beta-cell mass alone, is a key benefit of NPY1R activation by SL-PYY. Indeed, positive effects on beta-cell turnover were not different between treatment groups and observed effects on beta-cell proliferation and protection against apoptosis agree with earlier studies on the effects of these peptides on beta-cell health.…”
Section: Discussionsupporting
confidence: 87%
“…In this regard, peptide tyrosine (PYY), a 36 amino acid gut‐derived peptide secreted from L‐cells, binds to neuropeptide Y1 receptors (NPY1Rs) expressed on pancreatic beta cells to induce insulinostatic actions that promote beta‐cell rest 18 . Moreover, NPY1R signalling has been shown to enhance beta‐cell growth and survival, 18,19 as well as evoking positive islet cell transdifferentiation events that enhance beta‐cell mass 20 . To pharmacologically exploit such actions, dipeptidyl peptidase‐4 (DPP‐4) stabilized analogues of human PYY (1–36) were generated through astute amino acid modification, based on current structure/function knowledge for PYY 21 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, failure to suppress NPY expression in β cells during metabolic stress was identified to be crucial in accelerating the programming of cell death [ 28 ]. Intriguingly, previous studies reported that treatment of Y receptor agonists, such as PYY administration, appears to protect islet β cells from apoptosis and dedifferentiation triggered by STZ in diabetic mice [ [13] , [14] , [15] , 32 ]. Considering that the administration of PYY in diabetic mice induced significant weight loss, the mechanism underlying PYY's β-cell protective effects is likely attributable to its anorexic effect acting via the Y2 receptor rather than via the Y1 receptor on the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%